(3TQM eNJUQ GdSfhSi aj Yde GdefWbs - (3eMeO Hf jhSa Hf YeQ Hf TYjH GdMSfj GdSfhSj , CHh YHO Gddg, J (B895 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf jhSa GdSfhSi GdMeO ddg Gdedc GdhgGH Gdedge ddUhGH hHYO agPG JbjjO bUOJ Hg TQM eNJUQi ai Yde GdefWb HWQjb GdEjLGR hGdYOhd Yf GdEcKGQ s
(3BNQgG (B:s
(3bhdg HGMSGf GdeQGO GdCYeGd GdTQYjI bhdg Edi jhe GdbjGeI hjhe GdOjf GdeSei Hjhe GdLRGA hjhe GdMSGH hGdhGbYI hGdWGeI hGdMGbI hZjQ Pdc hTcQ GdefYe hGLH HGdTQY hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs